MANAGEMENT OF EXTRIMITY FRACTURE IN EMERGENCY DEPARTMENT - Parahita, Putu Sukma; Kurniyanta, Putu (E-Jurnal Medika Udayana; vol 2 no 9 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE Fracture injuries in the extremities are accounted for 40% of the incidence of fractures in the United States and causes high morbidity (physical suffering, lost time, and mental stress). High-energy fractures of the lower limbs can also cause life threatening condition like major vascular injury, crush syndrome, and compartment syndrome. Initial treatment in the emergency room is essential to save lives and to save the fractured extremities. Primary survey (securing the airway, breathing and circulation) and the secondary survey will be able to quickly and accurately identify dangerous early complication of fractures, such as major arterial injury, crush syndrome and compartment syndrome. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Fracture, Extrimities, Treatment, Emergency ?